FABRICATION AND INVESTIGATION OF OXYGEN SENSOR USED GOLD ARRAY MICROELECTRODE - Hà, Vũ Thị Thu; Nữ, Đặng Thị Tố (Vietnam Journal of Science and Technology, 2012)
SUMMARYThis paper presents the most recent results in manufacturing of oxygen sensor based on gold array microelectrode. Steps of sensor preparation were clearly shown.  The electrochemical behavior of home-made gold array microelectrodes in K3Fe(CN)6 medium with support electrolyte using cyclic voltammetry has been investigated. Several experimental parameters were conducted, such as investigation of sensor’s reproducibility, stability and linearity. RSD calculated after 10 measurements are 0.14 and 0.05 in the atmosphere and in oxygen free solution respectively. There  is an agreement between data received by home-made micro oxygen sensor and that by traditional Winkler titration.